KARAKTERISTIK PENDERITA HOSPITAL ACQUIRED PNEUMONIA DAN VENTILATOR ASSOCIATED PNEUMONIA YANG DISEBABKAN Acinetobacter baumannii DI INTENSIVE CARE UNITRSUP SANGLAH DAN POLA KEPEKAANNYA TERHADAP ANTIBIOTIK SELAMA NOVEMBER 2014 – JANUARI 2015 - Sherly Yunita; Dewa Made Sukrama (Universitas Udayana, 2015)
CHARACTERISTICS OF HOSPITAL ACQUIRED PNEUMONIA DAN VENTILATOR ASSOCIATED PNEUMONIAPATIENTS CAUSED BY Acinetobacter baumanniiIN THE INTENSIVE CARE UNIT RSUP SANGLAH AND SENSITIVITY PATTERN TO ANTIBIOTIC DURING NOVEMBER 2014 – JANUARI 2015Nowdays, the persistence of high antibiotics resistance cause increase morbidity pneumonia due to Acinetobacter baumanniiinfection.A. baumannii infection was susceptible to Intensive Care Unit (ICU) patients. This study was purposed to determine the characteristics of Hospital Acquired Pneumonia (HAP)and Ventilator Associated Pneumonia (VAP)patients in the ICU with sputum specimen positive A. baumannii in Sanglah hospitaland sensitivity pattern to antibiotics.This research used a descriptive epidemiological design. Data in this study used secondary data, culture results of sputum specimen in the Clinical Microbiology Installation Sanglah hospital and medical records of patients during November 2014 until January 2015.Two HAPpatients and five VAPpatients had characteristics were 57.14% male and 42.86% female, mean age was 52 years and 42.86% patients in group above 65 years old. Antibiotics that sensitive against A. baumannii including Amikacin (80%), Ampicillin/Sulbactam (100%), Cefoperazone/Sulbactam (60%), Trimethoprim/Sulfamethoxazole (60%), and Colistin (83,33%). While antibiotics were resistant including Cephalosporin generation III, Carbapenem, Gentamicin (60%), Levofloxacin (80%) and Amoxicillin/Clavulanic Acid (100%).It can be concluded that characteristics of HAP and VAPpatients with positive A. baumannii were male and female with age above 65 years old. Generally, resistant to betalaktam antibiotics and highly sensitive to polymyxin.